THE CHILDREN’S LANGUAGE SKILL OF INDONESIA AND JAVANESE - Sri Aju Indrowaty (Erudio Journal of Educational Innovation, 2018)
Javanese is the language of the Javanese people in Java, Indonesia. Various languages that affect the lifestyle of the Javanese people such as Indonesia (as the national language), English and other languages that are considered as popular, makes anyone who speaks Javanese is considered as old-fashioned. The ability in using Javanese language is annihilated by time, so that makes Javanese language is possible to extinct. This research examines the ability in using Javanese language among the children in growing age, evidenced by the ability to tell stories in two languages, which are Indonesia and Javanese. A descriptive-qualitative method is conducted to analyze the ability to telling a story by the children, 11 years old, in two languages;  Indonesia and Javanese language. The results of this research note that the ability in using  Indonesia is higher than in Javanese language, also the ability of a girl is higher than a boy. The discussion of language skills include the number of simple sentences, complex sentences, grammatical errors and borrowing words which are found from storytelling in two languages by boy and girl as respondents. From the data, the results, even though the children live in Java and have Javanese language as their mother tongue, the ability to use Javanese language is weaker than the ability to use Indonesia as the national language.